Environmental tobacco smoke exposure and health effects in children: results from the 1991 National Health Interview Survey. Issue 1 (1996) - Mannino, D M; Siegel, M; Husten, C; Rose, D; Etzel, R
Abstract : OBJECTIVE: To determine the effect of environmental tobacco smoke exposure on the health of children in the United States. DESIGN AND SETTING: Cross-sectional study of children who participated in the 1991 National Health Interview Survey. PARTICIPANTS: 17448 children residing in the United States. MAIN OUTCOME MEASURES: Rates of respiratory illnesses and all illnesses, and the morbidity due to these illnesses, in children exposed to environmental tobacco smoke in the home daily compared with those in children not exposed in the home. Our analyses controlled for age, socioeconomic status, race, family size, sex, season, and region of the country. RESULTS: Children who were exposed to environmental tobacco smoke had a higher incidence of acute respiratory illnesses (relative risk (RR) = 1.10, 95% confidence interval (CI) 0.95 to 1.26) and all chronic respiratory diseases (RR = 1.28, 95% CI 0.99 to 1.65) than children who were not exposed, although both CIs included unity, and chance cannot be ruled out as being responsible for these findings. Children who were exposed to environmental tobacco smoke had, on average, 1.87 more days of restricted activity (95% CI 0.20 to 3.54), 1.06 more days of bed confinement (95% CI 0.20 to 1.92), and 1.45 more days of school absence (95% CI 0.40 to 2.50) per year than children who were not exposed. CONCLUSIONS: Environmental tobacco smoke exposure in the home, which is completely preventable, is an important predictor of increased morbidity in children.